Provide a model for establishing a comprehensive knowledge management system in knowledge-based organizations based on success factors - Saeed Ghorbani; Shayan Naghdi Khanachah (Annals of Management and Organization Research, 2020)
Purpose: This study provides a model for establishing a comprehensive knowledge management system in knowledge-based organizations based on success factors. Research methodology: A researcher-made questionnaire was used to examine these factors and finally to present the model. The statistical population of this study is all managers and employees of knowledge-based organizations. There are 150 of them and 108 people were randomly selected as the research sample. Result: The results of factor analysis showed that all 7 factors under study explain 65.16% of the total variance, which is acceptable. On the other hand, the results of the Friedman test also showed the first to the seventh priority of effective factors of knowledge success in construction projects, including human resource development, knowledge-based orientation, knowledge evaluation and transfer, information systems infrastructure, business culture, modeling. Finally, there was a conflict between people. A model was designed according to the mentioned priority. Limitations: This research only described knowledge-based organizations. Contribution: In this article, using a comprehensive knowledge management system, an attempt is made to provide a mechanism for establishing and implementing a comprehensive knowledge management system in knowledge-based organizations to help it take an important step towards capacity building to create value in processes and exchanges. The knowledge of the experts of the organization should be removed in order to direct the tacit knowledge of the experts, which is the main capital of any organization, towards this important issue.